Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I work as an after school tutor at my high school. I've had kids come up to me asking how to do these types of problems:

$\left(\displaystyle \frac{5xy^{-2}}{3z^{-1}} \right)^{-2}$

My approach is to tell them to use the power of quotient rule:

$\left(\displaystyle \frac{a}{b} \right)^{n} = \displaystyle \frac{a^n}{b^n}$

$\displaystyle \frac{\left(5xy^{-2}\right)^{-2}} {\left(3z^{-1} \right)^{-2}}$

Then I tell them to use power of a product: $(a\cdot b)^{n} = a^{n}b^{n}$

$\displaystyle \frac{5^{-2} x^{-2} \left(y^{-2}\right)^{-2}}{3^{-2}\left(z^{-1} \right)^{-2}}$

Freshmen find these steps confusing and when they get to this step they don't even know what to do, but I thought these rules would be helpful. I even gave them examples of each rule. The tutoring hours after school are usually filled with people struggling in algebra. How could I explain it better?

share|improve this question
add comment

2 Answers 2

You may do it as follows:

$$\left(\displaystyle \frac{5xy^{-2}}{3z^{-1}} \right)^{-2} =\left(\frac{3z^{-1}}{5xy^{-2}}\right)^2=\left(\frac{3y^2}{5xz}\right)^2=\left(\frac{9y^4}{25x^2z^2}\right)$$ Note that $$\Box^{~\color{blue}{-\star}}=\frac{1}{\Box^{~\color{red}{+\star}}}$$

share|improve this answer
    
Nice and very clear answer! –  Sami Ben Romdhane Jan 17 at 15:48
add comment

You could start off by showing them this...Using the rule $$\frac{a^n}{a^m}=a^{n-m}$$ $($I'm assuming that they are okay with the rule associated with dividing expressions with the same base$)$: $$a^3\div a^5=a^{3-5}=a^{-2}\space \text{and}\space a^3\div a^5=\frac{a\times a\times a}{a\times a\times a\times a\times a}=\frac{1}{a^2}\\ \text{so clearly}\\ a^{-2}=\frac{1}{a^2}$$ You can do some more examples, maybe two or three to give them some more intuition. Then you can introduce the general rule: $$a^{-n}=\frac{1}{a^n}$$

Now tackle the questions in steps.

$$\left(\frac{5xy^{-2}}{3z^{-1}}\right)^{-2}=\left(\frac{5x(y^{-2})}{3(z^{-1})}\right)^{-2}$$

Add brackets here so that they do not get confused and understand that only $y$ and $z$ are being raised to $-2$ and $-1$ in the numerator and denominator respectively. Now using the general rule for negative exponents from above, inside the brackets can be re-written and simplified as:

$$\left(\frac{5x(y^{-2})}{3(z^{-1})}\right)=\frac{5x\left(\frac{1}{y^2}\right)}{3\left(\frac{1}{z^1}\right)}=\frac{5x}{y^2} \div \frac{3}{z}=\frac{5x}{y^2}\cdot\frac{z}{3}=\frac{5xz}{3y^2}$$

Now you have the simplified expression of the inner brackets raised to $-2$. Apply the general rule again to get: $$\left(\frac{5xz}{3y^2}\right)^{-2}=\frac{1}{\left(\frac{5xz}{3y^2}\right)^{2}}$$

Now for the denominator..Give them some computations of the form $\frac{a^n}{b^n}$, $\left(\frac{a}{b}\right)^n$ and $a^nb^n$, $(ab)^n$ maybe three or four examples. After computing these, they should intuitively begin to realize that $\frac{a^n}{b^n}=\left(\frac{a}{b}\right)^n$ and $a^nb^n=(ab)^n$. After that you can explain to them that this is so $($i.e. they hold$)$ because of the power of quotient rule and power of a product rule respectively.

Applying this to the denominator it becomes: $$\left(\frac{5xz}{3y^2}\right)^{2}=\frac{(5xz)^2}{(3y^2)^2}=\frac{5^2x^2z^2}{3^2(y^2)^2}=\frac{5^2x^2z^2}{3^2y^4}$$

Here you can stress that when an expression is raised to a power, you need to raise everything in the expression to the power. And that is why $(3y^2)^2=3^2(y^2)^2=3^2y^{2(2)}=3^2y^4$

Alternately if they are still not following why $a^nb^n=(ab)^n$, another way to look at it could be like this. If you have $(ab)^2$ this is the same as multiplying "$ab$" by itself twice..If you have $(ab)^3$ this is the same as multiplying "$ab$" by itself thrice and so on and so on. So $$(5xz)^2=(5xz)(5xz)=25x^2z^2,\space {}\space (3y^2)^2=(3y^2)(3y^2)=9y^4$$

Simplifying the last bit becomes $$\frac{5^2x^2z^2}{3^2y^4}=\frac{25x^2z^2}{9y^4}$$

But remember that was just the denominator and it is being divided by $1$, so: $$\frac{1}{\frac{25x^2z^2}{9y^4}}=1\div \frac{25x^2z^2}{9y^4}=1\cdot\frac{9y^4}{25x^2z^2}=\frac{9y^4}{25x^2z^2}$$

share|improve this answer
1  
Complete source and good points. +1 –  B. S. Jan 17 at 16:58
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.